PROBLEMATIKA INTEGRASI MAZHAB FILSAFAT PENDIDIKAN DALAM PENDIDIKAN ISLAM - Pefriani Pefriani; Juliana Sari Caniago; Mufidah Hannum Nst; Safrina Harahap; Pahri Siregar (PT Inovasi Pratama Internasional, 2026)
This study aims to analyze the characteristics of schools in educational philosophy and their implications for Islamic education. This study uses a qualitative approach with the type of library research, which is sourced from books, scientific journals, and other relevant literature. The data was analyzed descriptively and comparatively to identify the differences, similarities, and contributions of each school. The results show that the philosophy of education is divided into two main tendencies, namely traditional (essentialism and perennialism) that emphasizes the stability of values and the dominant role of educators, and contemporary (progressivism, existentialism, and reconstructionalism) which is oriented towards individual freedom, learning experience, and social change. In the context of Islamic education, each school has its relevance as well as its limitations. Traditional schools are aligned with efforts to maintain basic Islamic values, while contemporary schools contribute to the development of more adaptive and contextual learning methods. However, the difference in paradigm between schools requires a proper selection and integration process so as not to conflict with Islamic principles. This study concludes that an integrative approach that combines traditional values with modern thinking becomes a strategic solution in the development of relevant, adaptive, and sustainable Islamic education.